2020
DOI: 10.1111/1346-8138.15322
|View full text |Cite
|
Sign up to set email alerts
|

Case series of cutaneous T‐cell lymphomas treated with bexarotene‐based therapy

Abstract: Bexarotene is useful for both early and advanced cutaneous T-cell lymphoma (CTCL), and is sometimes applied to ultraviolet-tolerant early CTCL patients as one of the first-line therapies in the real world. However, continuous administration of bexarotene is sometimes difficult because of its adverse events (AE). Development of an appropriate protocol for bexarotene that can induce a consistent response for CTCL without severe AE (SAE) is needed. We retrospectively investigated 29 Japanese cases of CTCL and eva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 14 publications
3
17
0
Order By: Relevance
“…SAE (grade 3 and 4) developed in 23.8% of the regular‐dose cohort and 12.5% of the low‐dose cohort. Mean event‐free survival of the low‐dose cohort was prolonged compared with the regular‐dose cohort (19.1 months [95% CI, 8.7–29.5] vs. 6.7 months [95% CI, 3.6–9.7]) 16 . Consequently, these results suggest that a combination of low‐dose bexarotene plus NBUVB therapy provides a promising therapeutic option for safety reasons 16 …”
Section: Discussionmentioning
confidence: 91%
“…SAE (grade 3 and 4) developed in 23.8% of the regular‐dose cohort and 12.5% of the low‐dose cohort. Mean event‐free survival of the low‐dose cohort was prolonged compared with the regular‐dose cohort (19.1 months [95% CI, 8.7–29.5] vs. 6.7 months [95% CI, 3.6–9.7]) 16 . Consequently, these results suggest that a combination of low‐dose bexarotene plus NBUVB therapy provides a promising therapeutic option for safety reasons 16 …”
Section: Discussionmentioning
confidence: 91%
“…The subjects in this study had a high proportion of early-stage MF and high response rates by mSWAT and PGA evaluation after 8 weeks, suggesting that early diagnosis and early treatment are necessary for CTCL treatment. A case series study performed by Fujimura et al indicated that a low initial dose of bexarotene (150-300 mg/body) combined with narrowband UVB could be an optimal treatment for advanced-stage CTCL [18]. These findings The results of the mSWAT and PGA evaluations after 8 weeks did not differ significantly between the two groups.…”
Section: Discussionmentioning
confidence: 89%
“…The incidences of SAEs ranged from 20.7 to 25.0% [54,63]. Overall, bexarotene is effective and well-tolerated for the treatment of patients with early-and advanced-stage CTCLs [54,60,62,63].…”
Section: Bexarotenementioning
confidence: 97%
“…The most frequent drug-related AEs were hypothyroidism (93.8-96.6%), hyperlipidemia (81.3-93.1%), and leukopenia (31.0-68.8%) [11,62]. The incidences of SAEs ranged from 20.7 to 25.0% [54,63]. Overall, bexarotene is effective and well-tolerated for the treatment of patients with early-and advanced-stage CTCLs [54,60,62,63].…”
Section: Bexarotenementioning
confidence: 99%
See 1 more Smart Citation